2011
DOI: 10.1128/aem.06047-11
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Intestinal and Extraintestinal Virulence Genes in Escherichia coli Isolates from Rainwater Tanks in Southeast Queensland, Australia

Abstract: In this study, 200 Escherichia coli isolates from 22 rainwater tank samples in Southeast Queensland, Australia, were tested for the presence of 20 virulence genes (VGs) associated with intestinal and extraintestinal pathotypes. In addition, E. coli isolates were also classified into phylogenetic groups based on the detection of the chuA, yjaA, and TSPE4.C2 genes. Of the 22 rainwater tanks, 8 (36%) and 5 (23%) were positive for the eaeA (belonging to enteropathogenic E. coli [EPEC] and Shiga-toxigenic E. coli [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 53 publications
(78 reference statements)
2
33
0
2
Order By: Relevance
“…isolated from rainwater tank samples (Ahmed et al . , ). Certain E. coli strains from rainwater tank samples harbouring virulence genes were identical to those found in possum and bird faeces (Ahmed et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…isolated from rainwater tank samples (Ahmed et al . , ). Certain E. coli strains from rainwater tank samples harbouring virulence genes were identical to those found in possum and bird faeces (Ahmed et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also reported the presence of clinically significant virulence genes associated with FIB in rainwater tank samples in SEQ (Ahmed et al . , ). Questions have, therefore, arisen regarding the persistence of FIB and pathogens in rainwater tank samples as well as in faecal deposits on the roof and in the gutter.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the environmental strains carrying estII and eltA genes also harbored genes such as hlyA and iroN E.coli , which are responsible for acquisition of iron and are commonly found among UPEC strains. Recently a number of studies have detected the presence of these and other VGs belonging to UPEC in surface and rain tank waters (1). Similarly, Masters et al (38) found a high level of these and other VGs in all three water types.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of the intimin eae gene in EPEC could indicate the presence of Shiga-toxin producing E. coli, since this gene is found in more than one pathotype (34). The ingestion of EPEC, however, causes watery diarrhea that is associated with vomiting and low fever (12), whereas EHEC represents one of the most pathogenic E. coli groups that have the ability to cause bloody diarrhea, with little or no fever.…”
Section: Discussionmentioning
confidence: 99%